1997
DOI: 10.1038/bjc.1997.48
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response study of ibandronate in the treatment of cancer-associated hypercalcaemia

Abstract: Summary Hypercalcaemia is an important cause of morbidity in malignant disease. We studied the efficacy and safety of intravenous ibandronate (a new, potent bisphosphonate) in a multicentre study of 147 patients with severe cancer-associated hypercalcaemia which had been resistant to treatment with rehydration alone. Of 131 randomized patients who were eligible for evaluation, 45 were allocated to receive 2 mg ibandronate, 44 patients to receive 4 mg and 42 patients to receive 6 mg. Serum calcium values fell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(55 citation statements)
references
References 28 publications
4
50
0
1
Order By: Relevance
“…O'Rourke et al (1993) found a differential response rate of only 50% in patients with humoral hypercalcaemia compared to 74% in patients with bone metastases and 100% in myeloma patients (one sixth of patients recruited). This effect has been reported by other studies (Body et al, 1987;Body and Dumon, 1994;Thiebaud et al, 1988;Ralston et al, 1997). In this study, no significant difference in response rate was seen between tumour types and patients with or without bone metastases but the number of patients in each group was small.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…O'Rourke et al (1993) found a differential response rate of only 50% in patients with humoral hypercalcaemia compared to 74% in patients with bone metastases and 100% in myeloma patients (one sixth of patients recruited). This effect has been reported by other studies (Body et al, 1987;Body and Dumon, 1994;Thiebaud et al, 1988;Ralston et al, 1997). In this study, no significant difference in response rate was seen between tumour types and patients with or without bone metastases but the number of patients in each group was small.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have explored dose response relationships for different bisphosphonates and degree of hypercalcaemia (Body et al, 1987(Body et al, , 1994(Body et al, , 1999Thiebaud et al, 1988;Nussbaum et al, 1993;Pecherstorfer et al, 1996;Ralston et al, 1988Ralston et al, , 1997. There have been few studies however exploring this dose response relationship for single dose clodronate, the majority of which have involved consecutive daily clodronate infusions rather than single dose comparisons (Adami et al, 1987;Urwin et al, 1987;Bonjour et al, 1988;Kanis et al, 1990).…”
mentioning
confidence: 99%
“…6 The rationale to use a dose of 6 mg ibandronate derives from the dose -response studies in the treatment of cancer-associated hypercalcemia. 20 -23 These investigations reported on a significantly reduced efficacy to restore normocalcemia in tumors other than breast cancer and hematological tumors since the osteolytic process responsible for hyperclacemia appears to be predominantly humeral in solid tumors; 21 hematological malignancies show mainly local osteolytic mechanisms and breast cancer demonstrates a mixed osteolytic process involved in hypercalcemia. 22,23 These hypothetical findings are paralleled by measurable disturbances in calcium metabolism in patients with PCA.…”
Section: Discussionmentioning
confidence: 99%
“…Single doses of ibandronate ranging from 0.2-6 mg via 2-to 4-hour infusions have been investigated in trials involving more than 300 patients [12]. A dose of 4-6 mg ibandronate (via a 2-hour infusion) was required to effectively normalize serum calcium levels in 75%-80% of patients with moderate-to-severe HCM (serum calcium ≥12 mg/dl) [36]. Serum creatinine elevations were reported in <1% of patients treated with ibandronate in those studies [12].…”
Section: Ibandronatementioning
confidence: 99%